2005
DOI: 10.1063/1.1909283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dielectric materials on stress-induced damage modes in damascene Cu lines

Abstract: The stress of damascene Cu integrated with silicon dioxide (SiO2) and a low-k material was analyzed by x-ray diffraction, and that of the via-line structure was evaluated using finite element analysis. In both cases, the hydrostatic stress of the Cu line embedded in SiO2 was greater than that of the Cu line with low-k dielectric, whereas the opposite was true for the von Mises stress. In particular, the von Mises stress in the via embedded in the low-k dielectric was large. It was also shown that the yield str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…So far this has turned out not to be the case. However, we argue that the present data are qualitatively consistent with previously reported calculations [6,7] and measurements [8,9] of stresses in damascene structures.…”
Section: Introductionsupporting
confidence: 93%
“…So far this has turned out not to be the case. However, we argue that the present data are qualitatively consistent with previously reported calculations [6,7] and measurements [8,9] of stresses in damascene structures.…”
Section: Introductionsupporting
confidence: 93%
“…However, larger stress values ͑500-600 MPa͒ that appear biaxial ͑ 11 = 22 ͒ in narrow Cu lines within porous low-k dielectrics were reported by Wilson et al,4 suggesting that the Cu was highly constrained in the transverse direction despite the presence of a highly compliant dielectric material adjacent to the lines. While Cu out-ofplane stress ͑ 33 ͒ values were consistently tensile in low-k dielectric arrays, 3 those embedded in porous low-k dielectrics appeared to switch from compressive to tensile over the range of measured linewidths. 4 In an effort to resolve these discrepancies, the current study was undertaken to perform a more through examination of the impact of smaller linewidth on stress in Cu arrays at technologically relevant dimensions.…”
Section: Triaxial Stress Distributions In Cu/low-k Interconnect Featuresmentioning
confidence: 84%
“…Paik et al 3 indicated that in narrow Cu lines with organosilicate glass ͑OSG͒ dielectric material, the transverse stresses ͑ 22 , 33 ͒ were similar and lower in magnitude than the corresponding longitudinal stress ͑ 11 ͒. However, larger stress values ͑500-600 MPa͒ that appear biaxial ͑ 11 = 22 ͒ in narrow Cu lines within porous low-k dielectrics were reported by Wilson et al,4 suggesting that the Cu was highly constrained in the transverse direction despite the presence of a highly compliant dielectric material adjacent to the lines.…”
Section: Triaxial Stress Distributions In Cu/low-k Interconnect Featuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Applying the curvature method to passivated (encapsulated) line structures have also been reported [70,[241][242][243]. The X-ray diffraction [63,83,86,87,[244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259], Raman spectroscopy [260,261], and micromachine-based [262] techniques have also been developed and employed in measuring stresses in specially designed metal line structures.…”
Section: Basic Considerationmentioning
confidence: 96%